New Techniques and Devices in Transjugular Intrahepatic Portosystemic Shunt Placement - RiChard, Jamie; Thornburg, Bartley (Seminars in Interventional Radiology, 2018)
Recently, new techniques and devices in transjugular intrahepatic portosystemic shunt (TIPS) placement have emerged that can improve upon the standard procedure. Ultrasound guidance during TIPS with intracardiac echocardiography (ICE), placement of controlled expansion (CX) stents, and portal vein recanalization (PVR) via transsplenic access are three techniques with new data supporting their implementation. ICE guidance can improve the technical success of difficult cases, decrease procedure time, and decrease complications such as capsular puncture, hemobilia, and hepatic artery injury. CX stents offer the operator better control over the final portosystemic gradient, which is particularly useful in patients with a high risk of post-TIPS hepatic encephalopathy. Finally, transsplenic access provides a stable, antegrade route for PVR, which can be used to optimize transplant candidacy as well as treat the sequelae of portal hypertension in patients with portal vein thrombosis. This article will describe the benefits, technical parameters, and patient selection criteria for each of these new techniques.
Keywords: TIPS; portal hypertension; intravascular ultrasound; portal vein thrombosis; transsplenic